The relationship between the severity and specific dimensions of OCD in Iranian clinical sample - Rashid, Sajjad; Khosheh, Mohsen; Khorramdel, Kazem; Hosseini, Sayed mehdi; Amiri, Farzad (Researcher Bulletin of Medical Sciences, 2018)
Background: There have been a few studies that examined the association between insight and the clinical symptoms of obsessive-compulsive disorder (OCD) among the Middle Eastern population. The current study aimed to find a relationship between insight, general score and the specific dimensions of OCD among Iranian clinical sample. Method: The cross-sectional research method was conducted on 108 OCD patients from 18 to 61 years old. Participants were interviewed with a semi-structured interview based on DSM-V, and those who were diagnosed with other psychiatric disorders were excluded. Also, participants filled out some self-report scales including Obsessive-Compulsive Inventory-Revised, Overall Anxiety Severity and Impairment Scale and Beck Depression-II Inventory. Result: The results showed that poor insight has a relationship with OCD symptoms except for hoarding. Moreover, anxiety was significantly correlated with the severity of OCD.